Assessment of Treatment Outcomes of Interstitial Cystitis with Sodium Hyaluronate by The O’leary-Sant Interstitial Cystitis Symptom Index (ICSI) and Interstitial Cystitis Problem Index (ICPI)) - Fuad Hariyanto; M Surya Negara (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2021)
Objective: To assess the treatment outcome of interstitial cystitis with sodium hyaluronate (cystistat) installation by O’Leary-Sant interstitial cystitis symptom index (ICSI) and interstitial cystitis problem index (ICPI).Material and methods: From January 2019 to October 2020, 11 patients diagnosed with interstitial cystitis were treated with sodium hyaluronate (cystistat) installation. Each patient was assessed using the O’Leary-Sant interstitial cystitis symptom index (ICSI) and interstitial cystitis problem index (ICPI) before and after therapy.Results: The number of interstitial cystitis patients who completed the installation program in this study was 11 patients. In the assessment of interstitial cystitis symptom index (ICSI), there was a significant clinical improvement in each of the symptoms, which are urgency, frequency, nocturia, and bladder pain, with statistical test results obtained p-value (0.002, 0.003, 0.003, and 0.003) consecutively. In the interstitial cystitis problem index (ICPI) study, clinical improvements were obtained from each symptom in the form of urgency, frequency, nocturia, and bladder pain with statistical test results obtained p-value (0.002, 0.003, 0.003, and 0.003) consecutively.Conclusion: In all interstitial cystitis patients who were treated with sodium hyaluronate installation in this study, there was a significant difference in the values of O’Leary-Sant interstitial cystitis symptom index (ICSI) and interstitial cystitis problem index (ICPI) before and after therapy. This shows that sodium hyaluronate (cystistat) installation therapy is very effective for interstitial cystitis patients.